Long-term outcome of catheter ablation in patients with persistent atrial fibrillation and functional tricuspid regurgitation - Liu, Wenwu; Wang, Anlu; Li, Qiuyi; Zhang, Qitong; Chen, Songwen; Wei, Yong; Lu, Xiaofeng; Wu, Xiaoyu; Dai, Bin; Liu, Shaowen; Zhou, Genqinq (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAtrial fibrillation (AF) and tricuspid regurgitation (TR) frequently coexist and mutually worsen each other. However, the long-term effects of functional tricuspid regurgitation (FTR) on AF recurrence and the improvement of TR after radiofrequency catheter ablation (RFCA) remain unclear.MethodsThis retrospective, single-center observational study involved 1,690 patients with persistent atrial fibrillation (PsAF) who underwent AF ablation between January 2012 and June 2022. 153 paients with significant FTR were propensity matching 153 patients with no or mild FTR based on age, body mass index, and mitral regurgitation (MR) severity. Patients were followed up for at least 1 year. Procedural success was defined as freedom from any atrial tachyarrhythmia (>30 s) after the 3-month blanking period, off antiarrhythmic drugs. Significant FTR was defined as moderate to severe TR. Significant TR improvement was defined as a reduction in TR severity by ≥2 grades from pre- to post-ablation.ResultsAmong the observational cohort, 153 patients (9.1%) had significant FTR, the severity of which correlated with female sex, AF duration, atrial/ventricular remodeling, and NT-proBNP levels. During the 12-month follow-up, the procedural success rate was 67.6% (207/306). RFCA significantly reduced the proportion of RA and RV enlargement (P < 0.001), and improved the severity of FTR (P < 0.001). Logistic regression analyses showed that AF recurrence [odds ratio (OR) 18.244, 95% CI 7.500–52.427, P < 0.001]) was the strongest independent risk factor for non-significant TR improvement after ablation. After a mean follow-up of 5.3 ± 3.7 years, the overall procedural success rate was 47.4% (145/306). The overall success rate was significantly lower in patients with significant FTR compared to those with no or mild FTR (37.3% VS 57.5%, P < 0.001). A comparable difference was observed between ventricular FTR and no or atrial FTR (27.1% VS 53.4%, P < 0.001).ConclusionsSignificant FTR was an independent predictor of AF recurrence in patients with PsAF undergoing RFCA. The long-term success was poor in the subgroups of significant FTR and those with ventricular FTR. Furthermore, successful RFCA was associated with significantly improved FTR in patients with PsAF.